Hubungan Tingkat Pengetahuan Kesehatan Dan Keselamatan Kerja Dengan Kesiapsiagaan Bencana Kebakaran Pada Karyawan - Kaloka, Shagita; Cahyadi Setiawan; Ahman Sya (Geography Education Study Program, Universitas Kanjuruhan Malang, 2025)
This study aims to examine the relationship between occupational health and safety (OHS) knowledge and fire disaster preparedness among employees at the Directorate of Labor Norm Inspection, Ministry of Manpower of the Republic of Indonesia. The research method used is descriptive with a correlational design. The population consists of all employees at the Directorate, with a total sampling technique involving 49 respondents. The results show a significant positive relationship between OHS knowledge and fire preparedness, with a correlation coefficient (r) of 0.398, indicating a weak but significant relationship at the 0.005 significance level (p < 0.01). The lowest level of OHS knowledge recorded was 10%, while the lowest preparedness aspect was in the emergency response plan indicator, at 59%. Based on these findings, it is recommended that the organization enhance OHS training—particularly regarding machinery and work equipment-and improve the development and dissemination of emergency response plans for all employees.